2020
DOI: 10.3390/rel11030139
|View full text |Cite
|
Sign up to set email alerts
|

Item Response Theory Applied to the Spiritual Needs Questionnaire (SpNQ) in Portuguese

Abstract: The item response theory (IRT), or latent trace theory, is based on a set of mathematical models to complement the qualitative analysis of the items in a given questionnaire. This study analyzes the items of the Spiritual Needs Questionnaire (SpNQ) in the Portuguese version, applied to HIV+ patients, with R Studio 3.4.1, mirt statistical package, to find out if the items of the SpNQ possess appropriate psychometric qualities to discriminate between respondents as to the probability of marking one answer and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Although IRT has demonstrated its utility in the field of psychometric research, it has only been applied to evaluate the psychometric characteristics of the Spiritual Needs Questionnaire (SpNQ) in its Portuguese version for HIV + patients in Oliveira da Silva’s (2020) study. The study showed that the SpNQ items were appropriately discriminating and had varying levels of difficulty, indicating that the questionnaire has good psychometric properties [ 53 ]. This suggests that IRT could and should be utilized to enhance the quality of assessment questionnaires related to patients’ spiritual needs [ 103 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although IRT has demonstrated its utility in the field of psychometric research, it has only been applied to evaluate the psychometric characteristics of the Spiritual Needs Questionnaire (SpNQ) in its Portuguese version for HIV + patients in Oliveira da Silva’s (2020) study. The study showed that the SpNQ items were appropriately discriminating and had varying levels of difficulty, indicating that the questionnaire has good psychometric properties [ 53 ]. This suggests that IRT could and should be utilized to enhance the quality of assessment questionnaires related to patients’ spiritual needs [ 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…Muslims view spirituality and religion (beliefs and practices) as inseparable and do not distinguish between the two concepts [ 52 ]; in fact, the concept of religion is intertwined with spirituality [ 43 ]. It should be noted that only Oliveira da Silva’s (2020) study employed item response theory to validate the Portuguese version of the SpNQ for use among patients with HIV [ 53 ]. IRT can be an effective approach for developing, assessing, and refining questionnaires, producing precise, valid, and relatively brief instruments that minimize response burden [ 54 ].…”
Section: Introductionmentioning
confidence: 99%